Management Of Organizational Performance: The Role Of Human Resource Management Strategy - Andri Goklas; Setyo Riyanto; Jenny Sihombing; E Nurzaman AM; Denok Sunarsi (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
Human resource management practices are important to determine strategic competition, business sustainability, and tight global issues. Companies that properly apply human resource management practices will compete and win an increasingly fierce business war. There are four approaches to human resource management practices: universalist, contingency, configuration, and contextual. The four approaches provide an important role and contribution in shaping the uniqueness of the company's position in business competition to improve medium and long-term performance. This study has shown that companies with the right and effective implementation or practice of human resource management strategy will improve company performance. This paper provides additional references for researchers as well as to the practitioner environment.